Reprezentacja muzyczna a filozofia umysłu - Szubart, Tomasz (Filozofia Nauki, 2019)
Representation is one of the key concepts in cognitive science and philosophy of mind. The philosophical problem of musical meaning, or rather its naturalistic reformulation, has only recently become the topic of empirical investigation. It might seem obvious that an explication of the concept of meaning would appeal to the concept of representation. It is not a popular approach in the philosophy of the cognitive science of music, however. The aim of this paper is to provide an overview of possible frames of analysis of musical representation within selected contemporary paradigms in the broadly understood philosophy of mind and cognitive science.